Fiscal Arbitration as a Dispute Resolution Mechanism in Mexico - Reyes Santiago, José Raúl (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To determine if there is a legal impediment to applying fiscal arbitration as an alternative method of dispute resolution in Mexico. MATERIAL AND METHOD: The qualitative method, of documentary and descriptive type, was used. A review of secondary sources and the legal framework was carried out to answer the research question based on a deductive analysis. RESULTS: There is no constitutional impediment to applying fiscal arbitration in Mexico, as a complementary and auxiliary method, but not a substitute for the jurisdictional route. CONCLUSIONS: The use of fiscal arbitration in Mexico is pertinent, to offer taxpayers a faster and more agile method of resolving disputes, avoiding wasting time, and unnecessary economic wear, and tear, and guaranteeing full access to justice.